Effectiveness of Group Counseling Services Using Self-Instruction Techniques to Reduce Students Academic Procrastination in Grade XI at SMAN 7 Kediri - Mony, Wadra; Wijaya, Intan Prastihastari; Putri, Ayu Febrika Eka (Lembaga KITA, 2025)
High levels of academic procrastination among students need to be addressed to ensure the effectiveness of group counseling services. A reduction in procrastination is reflected in more active participation during learning, improved planning and time management, as well as better quality of assignments and academic outcomes. This research aimed to reduce academic procrastination by applying group counseling methods combined with self-instruction techniques. The study employed an experimental approach within the framework of action research in guidance and counseling. Participants consisted of four students identified as having high levels of academic procrastination. Data were collected using self-evaluation questionnaires and analyzed both descriptively and comparatively. The findings revealed notable differences between the pre-cycle, first cycle, and second cycle. Initial (pre-test) results indicated that students' procrastination scores fell within the high to very high categories (54, 53, 57, 62). By the second cycle, these scores had decreased to the very low category (18, 18, 16, 21). This demonstrates a substantial reduction in academic procrastination following the intervention. However, as the study involved only four participants, the results may not fully represent the broader student population. It is hoped that these findings will encourage students to become more aware of their own study habits. Guidance and counseling teachers are encouraged to design engaging and relevant services that foster a comfortable environment for students to share their experiences. Future research should consider involving more diverse participants and exploring alternative techniques or approaches that might be even more effective in addressing academic procrastination. The use of group counseling with self-instruction techniques has shown promise in helping students manage and reduce academic procrastination